DAMPAK SOSIAL EKONOMI PEMBANGUNAN OBJEK WISATA RELIGI PATUNG YESUS DI TANA TORAJA - Maria Yosmianti Paba; Abdul Rahman (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2019)
This study aims to know; 1) Background to the establishment of a religious statue of the Jesus statue in the village of Buntu Burake, Makale District, TanaToraja Regency; 2) Status and social role of the community around religious tourism objects before and after the construction project of Jesus statue religious tourism object in the dead-end village of Makale, Makale District, Tana Toraja Regency; 3) Impact of the socio-economic conditions of the community around the statue of the religious object of Jesus in the village of Buntu Burake, Makale District, Tana Toraja Regency. This study uses a type of qualitative research with descriptive type. The data collection technique was obtained by field research which included observation, documentation, and interviews involving 10 people who were included in the criteria of informants, namely the former Head of Burake, Lurah Burake, Burake community leaders, and the Burake community. The results of this study indicate that; 1) the establishment of a religious statue of a Jesus statue is the result of a government and community inspired by religious ceremonies and religious symbols in the Christian community, which in the process also adheres to the traditional rules that apply in the local community; 2) the status and social role of the community in Burake sub-district both before and after the construction of a statue of a religious statue of Jesus still has the same view that the community is not distinguished, either for people who have economic standards that are more or less people who have high social status based on descent, because based on the trust of the local community they are a family originating from the same family house (tongkonan); 3) the impact of the socio-economic conditions of the people of Burake before and after the construction project of the religious statue of Jesus statue is a clearly visible change in the economic condition of the Burake community which has increased and also the conditions around them where there has been an increase in the quality of their welfare public infrastructure for the local community.